Cellular Stress Response and Immune Signaling in Retinal Ischemia–Reperfusion Injury - Minhas, Gillipsie; Sharma, Jyoti; Khan, Nooruddin (Frontiers in Immunology, 2016)
Ischemia-reperfusion injury is a well-known pathological hallmark associated with diabetic retinopathy, glaucoma and other related retinopathies that ultimately can lead to visual impairment and vision loss. Retinal ischemia pathogenesis involves a cascade of detrimental events that include energy failure, excitotoxic damage, calcium imbalance, oxidative stress and eventually cell death. Retina for a long time has been known to be an immune privileged site; however, recent investigations reveal that retina, as well as the central nervous system (CNS), elicits immunological responses during various stress cues. Stress condition such as reperfusion of blood supply post-ischemia results in the sequestration of various immune cells, inflammatory mediators including cytokines, chemokines etc., to the ischemic region, which in turn facilitates induction of inflammatory conditions in these tissues. The immunological activation during injury or stress per se is beneficial for repair and maintenance of cellular homeostasis but whether the associated inflammation is good or bad, during ischemia-reperfusion injury, hitherto remains to be explored. Keeping all these notions in mind the current review tries to address the immune response and host stress response mechanisms involved in ischemia-reperfusion injury with the focus on the retina.